Impact of third wave of COVID-19 pandemic on mental health and its related lifestyle: a cross sectional survey - Rath, Padmalaya; Gautam, Shweta; Jain, Shruti; Bajpai, Anurag; Singh, Mohan; Kaushik, Subhash (International Journal Of Community Medicine And Public Health, 2023)
Background: The coronavirus outbreak has a detrimental impact on human life. Various measures have been taken to reduce socioeconomic impact, but many problems still persist especially mental health, in particular anxiety. The aim of this study was to examine the prevalence and contributing factors of anxiety among the people aged 18 and above, residents of Noida, during the third wave of COVID-19. Methods: This was descriptive cross-sectional study with semi structured questionnaire, completed by 401 participants. The questionnaire covered four parts: dysfunctional anxiety, mental health-related lifestyle changes, the indicators of negative mental health impact, and social and family support. Results: The mean age of participants was 36.9±11.5, and 34.2%, aged between 18 and 30 years. Of 401 participants, only 29 participants (i.e., 7.2%) reported CAS≥9 indicating anxiety. CAS is significantly higher in females, housewives and non-working group. Also, 53% of respondents reported that the pandemic had worsened their financial burden. There was an association between some of the sociodemographic variables and anxiety, different responses of lifestyle choices, negative health impact and social and family support. Conclusions: The pandemic had some positive results such as impact on social and family support, awareness of mental health issues and lifestyle changes. These positive results might operate as effective defences against the adverse COVID-19 effect. Further studies are required to investigate the positive impacts attributed to COVID-19 which can be supported.